Norovirus outbreaks in german refugee camps in 2015 - Grote, Ulrike; Schleenvoigt, Benjamin Thomas; Happle, Christine; Dopfer, Christian; Wetzke, Martin; Ahrenstorf, Gerrit; Holst, Hanna; Pletz, Mathias Wilhelm; Schmidt, Reinhold Ernst; Behrens, Georg MN; Jablonka, Alexandra (Zeitschrift für Gastroenterologie, 2017)
Purpose Refugees often live in confined housing conditions with shared kitchen and sanitary facilities, rendering susceptible to communicable diseases. We here describe the outbreak, spread and self-limiting nature of a norovirus outbreak in a German refugee camp in the winter of 2015.Methods During a norovirus outbreak, data on clinical symptoms, nationality and living conditions was obtained in a refugee camp in northern Germany in the winter of 2015. Furthermore secondary data on norovirus outbreaks in 2015 was assessed.Results Amongst n = 982 refugees, n = 36 patients (3.7 %) presented with acute norovirus gastroenteritis. The vast majority of cases were children, only the first patient was admitted to the hospital. Intensified hygiene measures were implemented on day 2 of the outbreak, but new cases peaked on day 21 and occurred until one month after the first case. Different cultural backgrounds, eating habits and hygiene standards amongst the refugees made it particularly challenging to implement stringent isolation and hygiene measures. Despite these predisposing factors, only minor norovirus outbreaks were reported in refugee camps in 2015.Conclusion Adults refugees had a low attack rate of symptomatic norovirus infection, while small children are at high risk. Infection spreads despite hygiene measures and camp sites and staff should be prepared for the particular challenges of such situations with a particular focus on cultural-background specific implementation of hygiene measures.
Keywords: Flüchtling; Asylbewerber; Norwalk; Noro; Gastroenteritis; Diarrhoe